Play it again : a novel - Clark, Georgia (The Dial Press, 2026)
When four once-inseparable friends reunite twenty years after the community theater production that first brought them together, they discover fresh feelings, unfinished business, and plenty of offstage drama in this charming ensemble queer rom-com. Love always deserves an encore . As teens, Annie, Lola, Vicky, and Dylan stole the show in a legendary gender-swapped version of Rosencrantz and Guildenstern Are Dead . Two couples, one unforgettable summer: until the closing-night party tore them apart, and not all of them knew why. Now, with lives that look nothing like they imagined, the foursome is called home by their beloved director for a one-night-only revival to save the theater, and the town. Returning to Rhodes means facing everything they left behind: long-buried secrets, undeniable chemistry, and the chance to write a brand-new ending: together. Brimming with nostalgia, wit, and small-town sparkle, Play It Again is a heartwarming story of first love, second chances, and the magic of finding your way back to the stage: and to the ones who knew you best.